Pendidikan Agama Kristen dalam Perspektif Multikulturalisme di Sekolah - Jessy Yunus Dannari; Nur Sitti; Jimmi Mangosa; Hermita Ratte; Fersiani Kanda Bassang (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Christian Religious Education (CRE) in Indonesia plays a crucial role in shaping the character and morality of students. Considering the cultural and religious diversity in Indonesia, Christian religious education needs to be delivered with a multicultural perspective that emphasizes values of tolerance and respect for differences. This article aims to explore the implementation of Christian religious education in schools within the context of multiculturalism, and how this can help strengthen attitudes of tolerance and interfaith harmony. This study also discusses the challenges in implementing multicultural-based Christian religious education and how practical solutions can be applied.